Integrated framework studying contribution of information system to firm performance - Ansar Daghouri; Khalifa Mansouri (Institute of Advanced Engineering and Science, 2022)
The main purpose of this paper is to study the correlation between information system (IS) success and firm performance based on two evaluation models already construct. The first model allowed to define the criteria and sub-criteria for evaluating the firm performance and the second model consisted of evaluating the IS success. Our contribution is to formalize a decision-making process based on the criteria of the two models as well as the weights generated by the implementation of the analytic hierarchy process (AHP) method to construct the influence diagrams that will allow us to trace the causal links between the two models. This approach has been implemented in three sectors chosen according to their use of information systems. The results obtained confirmed that the evaluation models are sectorial and therefore even the influence diagrams, hence the difficulty of studying the contribution of the IS success in achieving the firm performance with a general and generic approach.